2014
DOI: 10.1002/ams2.88
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the conventional Macintosh laryngoscope, the Pentax Airwayscope, and the McGrath MAC video laryngoscope under restricted cervical motion: a manikin study

Abstract: Aim:We compared the utility of the conventional Macintosh laryngoscope, the Pentax Airway Scope, and the McGrath MAC video laryngoscope under restricted cervical motion using a manikin. Methods:We recruited 36 participants into the simulation study. The manikin's cervical motion was restricted with a cervical collar and a head immobilizer, as occurs in trauma cases. We recorded the time to intubation and the success rate of the intubations.Results: Data are medians and ranges. The time to intubation under norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is intuitive to think that DL is a difficult skill to acquire and, VL must be an easier technique for novice trainees to learn. The studies of the learning protocol in normal airway and simulated difficult airway mannequin model usually results in superiority of VL over DL (e.g., better view; shorter intubation times, higher overall success rate, less dental trauma and esophageal intubation) [207][208][209][210][211][212][213][214]. Meanwhile, practicing may improve DL and VL skill competency and the rating of overall ease of use for DL/VL.…”
Section: Learning Curve For Vs Techniquementioning
confidence: 99%
“…It is intuitive to think that DL is a difficult skill to acquire and, VL must be an easier technique for novice trainees to learn. The studies of the learning protocol in normal airway and simulated difficult airway mannequin model usually results in superiority of VL over DL (e.g., better view; shorter intubation times, higher overall success rate, less dental trauma and esophageal intubation) [207][208][209][210][211][212][213][214]. Meanwhile, practicing may improve DL and VL skill competency and the rating of overall ease of use for DL/VL.…”
Section: Learning Curve For Vs Techniquementioning
confidence: 99%
“…15,16 Previous studies have also reported the AIRWAY SCOPE's superiority in terms of intubation time compared to other video laryngoscopes. 17,18,19,20 However, it is crucial to consider that the differences in intubation times might not be clinically signi cant, as all devices demonstrated a high success rate in both normal and di cult airway models.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the use of a manikin model may not fully represent the complexities and challenges of intubating human subjects, particularly in di cult airway scenarios. 9,12,14,17,20,25 Therefore, the generalizability of our ndings to clinical practice should be approached cautiously. Secondly, the study only involved novice healthcare providers, and the results may not be applicable to experienced providers.…”
Section: Discussionmentioning
confidence: 99%